Family childhood spatial conflict: A case study of young children's adaptation to family rules based on self-parenting diaries. Issue 2 (June 2023) - Zheng, Suhua
The family is often thought of as a private space. Relatively little research has been done on the childhood space of the family. Although the family is often considered a warm haven for children to grow up in, it is also a space for child-adult conflict. Based on the researcher's self-parenting diary, this paper uses thematic analysis and discourse critique to explore a 4-year-old girl's triggering, adapting, and even challenging of family rules in a Chinese family, in an attempt to demonstrate parent-child conflict in the family childhood space and explore its manifestations. The study found that families contain a variety of implicit rules, which are usually set and interpreted by parents. Four-year-olds differ from their parents in their understanding of family rules. Young children are predominantly passive adapters when it comes to health and hygiene; in play, they are allowed to show more agency and have more room for negotiation.